Assessing Microbial Uptake of Petroleum Hydrocarbons in Groundwater Systems Using Natural Abundance Radiocarbon - Ahad, Jason M. E.; Burns, Leanne; Mancini, Silvia; Slater, Greg F. (ENVIRONMENTAL SCIENCE & TECHNOLOGY, 2010)
Carbon sources utilized by the active microbial communities in shallow groundwater systems underlying three petroleum service stations were characterized using natural abundance radiocarbon ((14)C). Total organic carbon (TOC) Delta(14)C values ranged from -314 to -972 parts per thousand and petroleum-extracted residues (EXT-RES) ranged from -293 to -971 parts per thousand. Phospholipid fatty acids (PLFAs)-biomarkers for active microbial populations-ranged from -405 to -885 parts per thousand and a comparison of these values with potential carbon sources pointed to significant microbial assimilation of (14)C-free fossil carbon. The most (14)C depleted PLFAs were found in the samples with the highest concentrations of total petroleum hydrocarbons (TPHs). A radiocarbon mass balance indicated up to 43% of the carbon in microbial PLFAs was derived from TPHs, providing direct evidence for biodegradation at two of three sites. At lower levels of TPHs. Delta(14)C values of PLFAs were generally similar to or more enriched than all other carbon in the system indicating microbial utilization of a more (14)C-enriched carbon source and no resolvable evidence for microbial incorporation of petroleum-derived carbon. Results from this study suggest that it is possible to delineate petroleum biodegradation in groundwater systems using these techniques even in complex situations where there exists a wide range in the ages of natural organic matter (i.e., EXT-RES).